-27=7x-6

Simple and best practice solution for -27=7x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -27=7x-6 equation:


Simplifying
-27 = 7x + -6

Reorder the terms:
-27 = -6 + 7x

Solving
-27 = -6 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-27 + -7x = -6 + 7x + -7x

Combine like terms: 7x + -7x = 0
-27 + -7x = -6 + 0
-27 + -7x = -6

Add '27' to each side of the equation.
-27 + 27 + -7x = -6 + 27

Combine like terms: -27 + 27 = 0
0 + -7x = -6 + 27
-7x = -6 + 27

Combine like terms: -6 + 27 = 21
-7x = 21

Divide each side by '-7'.
x = -3

Simplifying
x = -3

See similar equations:

| 80=47.6r+8 | | 12x-4=11x+19 | | n+11=-81 | | ln(y)=-5*x+ln(c) | | =7(y+3) | | x-9+3(5x+4)=2(x+6) | | 3x(x-6)-(10x-6)= | | 3(-3x+2)=-7(x+3)-2 | | x^2-3-y=0 | | 0.25(x+2)-5=12 | | (10y+6)-(17y+8)= | | x^2+100x=0 | | (y^2+2y)(y^3-2y^2+1)= | | 5=20x+(10x*x) | | -2=0.2-6 | | 6x-4=23-3y | | x^2+12x+9=4 | | 3x-2=7x-3 | | 3a+5b=b+7b | | X+3=-12+6x | | 6(5x-11)=48x | | .25+X=45 | | 7m=2+5m | | -73=3e | | 10=-2x-2(-4x+4) | | 2(2w+3x)-3(2w-3x)= | | T(x)=19-(-3) | | 9m=-30+3m | | 4x+4+2x=9x+1 | | Y=7(x+1) | | 5x^3+43x^2-18x=0 | | 10m=28+3m |

Equations solver categories